Factors affecting Myrica faya Aiton demography in the Azores - Silva, Luís; Tavares, João (Sociedade Afonso Chaves, 1997)
Myrica faya (Myricaceae) is a small tree considered as an ibero-macaronesian endemic, a relic of the tethiano-tertiary flora. In the Azores M. faya stands are submitted to deforestation and to invasion by alien plants. In many stands density of Pittosporum undulatum, introduced from Australia, is higher than that of M. faya. In others, Hedychium gardneranum covers space between shrubs, impairing regeneration. Fruit production reaches 15x1000000 fruits/ha/year, and seed bank is of the same magnitude. Male flowers and fruits are predated by Argyresthía atlantícella. Mature fruits are eaten by Rattus rattus and Turdus merula azorensis. In the laboratory maximum germination after 65 weeks was 50%, but in the field, less than 1% of the fruits produced seedlings. In order to preserve M. faya stands and the associated fauna and flora, conservation measures should be immediately enforced.